Creatine kinase responses to training contest simulation in judo camps - Alfano, H. (1st scientific and professional conference on judo "Applicable research in judo" - Book of abstracts, 2015)
Creatine kinase concentration (CK) in blood is commonly reported as an indirect marker of muscle breakdown. Elevated levels of CK can suggest significant skeletal muscle damage. Previous research using CK markers in judo has suggested it may be a useful tool in evaluating effects of training in judo (Blach et al., 2007). Greater understanding of responses to training can allow for more informed training prescription.